Writing men : literary masculinities from Frankenstein to the new man - Schoene-Harwood, Berthold (Edinburgh University Press, 2000)
Comprising 14 individual case studies of work such as Heart of Darkness and Irvine Welsh's Marabou Stork Nightmares, this text gives a critical outline of the historical development of literary representations of masculinity.